Affecting Terrorism: Laughter, Lamentation, and Detestation as Drives to Terrorism Knowledge. Issue 3 (6th September 2017) - Heath-Kelly, Charlotte; Jarvis, Lee
Abstract: The contemporary fascination with terrorism in Anglo-American popular culture, political discourse, news reportage, and beyond is boundless and well documented. In this article, we explore contemporary productions of terrorism as the outcome of three drives to knowledge: laugher, lamentation, and detestation. Drawing on a range of social and cultural practices—including jokes, street art, film, memorial projects, elite rhetoric, and abuse scandals—we make two arguments. First, that humor, grief, and hatred underpin and saturate the contemporary desire to know terrorism. And, second, that—although these drives function in multiple and ambiguous ways—they serve to institute a distance between the subject and object of terrorism knowledge, not least by encouraging us to laugh at those punished for terrorism, mourn for those lost in attacks, and direct our hatred toward those responsible. This analysis not only opens fresh insight into the workings of terrorism discourse in the post-9/11 period, it also points to connections between contemporary "critical" work on terrorism and debate on the role of emotions and affect in international politics more broadly.